Association between antinuclear antibodies status and preterm birth in Japanese pregnant women: a prospective cohort study from Adjunct Study of the Japan Environment and Children’s Study - Mami Fukushige; Xi Lu; Minoru Satoh; Masako Oda; Takashi Ohba; Takahiko Katoh (BMC Pregnancy and Childbirth)
Abstract Background Antinuclear antibodies (ANA) are important biomarkers for the diagnosis of autoimmune diseases; however, the general population also tests positive at a low frequency, especially in women. Although the effects of various autoimmune diseases on pregnancy outcomes have been studied, the association of ANA with pregnancy outcomes in healthy individuals is unclear. Preterm birth (PTB), a major cause of neonatal death or long-term health problems, is a complex condition with a multifactorial etiology, and the underlying mechanism remains unclear. The present Adjunct Study aimed to determine the association between ANA and PTB in pregnant Japanese women based on a data analysis of the Japan Environment and Children’s Study. Methods In a prospective cohort design, we analyzed the demographic and pregnancy outcome data of 1085 pregnant Japanese women who were recruited between January 2011 and March 2014 in the Kumamoto University target area. Demographic data were collected using self-administered questionnaires and physician records. A serum ANA titer of ≥ 1:40 was defined as positive. Statistical analysis was performed by logistic regression analysis with PTB as the objective variable. Results The PTB rate was significantly higher in those who were ANA-positive (adjusted odds ratio, 2.06; 95% confidence interval, 1.09–3.87) than in those who were not. Conclusions This study suggests that ANA positivity in the first trimester of pregnancy is associated with an increased risk of PTB.